INOVASI PEMBELAJARAN DENGAN MENERAPKAN PROJECT BASED LEARNING PADA MATA KULIAH PEMROGRAMAN PEMBELAJARAN INTERAKTIF I - Budiharti Budiharti (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2014)
Interactive Learning programming is elective courses in Teacher Education courses and Elementary School Guidance and Counseling UPY with weights 2 credits . This subject is generally selected by students who are interested in learning computers . Applications used in this course is a Macromedia Authorware . To improve the quality of teaching and learning process by providing materials through project -based learning instructional model . Project Based Learning is a learning model which emphasizes student to be able to solve the problems actually encountered in the field . In this lesson the student will become a part of a professional who tries to solve problems in real life . Students create instructional media such as interactive CD learning . In making these media , students search for information related to the media being used in elementary schools that require interactive learning CDs . Through lectures by applying learning Project -based learning has produced instructional CD that can be used for learning in primary school . Through this learning process is not only the origin students make interactive multimedia instructional media , but the making of it is based on the results of an investigation of students . Through this course students are able to think creatively , independently and able to solve problems related to elementary school education.